CULPRIT-SHOCK: towards a “simplified” decision making of cardiogenic shock with multivessel coronary artery disease - Villablanca, Pedro A.; Flores, Pablo; Torres, Humberto; Villablanca, Salvador; Pedemonte, Oneglio (Journal of Emergency and Critical Care Medicine, 2018)
The incidence of cardiogenic shock (CS) as complication of acute myocardial infarction (AMI) involves 5% to 10% of cases and remains the main source of death in patients hospitalized with AMI (1), especially in those with multivessel (MV) coronary artery disease (CAD) (2).